2003
DOI: 10.1002/jcp.10397
|View full text |Cite
|
Sign up to set email alerts
|

Cationic polyelectrolyte hydrogel fosters fibroblast spreading, proliferation, and extracellular matrix production: Implications for tissue engineering

Abstract: Fibrous encapsulation is known to occur to many prosthetic implants and is thought to be due to the cells not adhering adequately to the surface. For developing new materials able to enhance cellular adhesion by mimicking extracellular matrix components, polyelectrolyte polymers, characterized by tunable surface charges, have been proposed. Here we demonstrate that panoply of cell functions over a two-dimensional substratum is influenced by surface charge. We have at first generated structurally related polyel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 44 publications
2
49
0
Order By: Relevance
“…33 Kapur and colleagues evaluated the passive adsorption of proteins in cell free culture medium to fluorinated ethylene propylene (FEP) and bacteriologicgrade polystyrene (PS). One explanation of this behavior of cell adhesion was that the titanium surface electrical charge affects the adsorbed protein layer composition, thus favoring the fibroblast adhesion to the positively charged titanium surface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…33 Kapur and colleagues evaluated the passive adsorption of proteins in cell free culture medium to fluorinated ethylene propylene (FEP) and bacteriologicgrade polystyrene (PS). One explanation of this behavior of cell adhesion was that the titanium surface electrical charge affects the adsorbed protein layer composition, thus favoring the fibroblast adhesion to the positively charged titanium surface.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21] The dentogingival fibers perpendicularly attached to the cementum form part of an abutment to the sulcular epithelium. 28,[32][33][34] However, variables inherent in chemically charged surfaces used in previous studies make it difficult to separate the electrical charge and chemical effects. It has been suggested that the creation of a perpendicular insertion of collagen fibers to the implant surface would enhance the barrier capacity and reduce the implant failure rate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In essence, these two situations allow the creation of cellular niches that simply permit cells to function or actively present cues that promote selected functions. To date, researchers have explored the development of hydrogels for the delivery of numerous primary cells, including chondrocytes Anseth, 2001, 2002;Bryant et al, 2004;Paige et al, 1995;Rice and Anseth, 2004;Sittinger et al, 2004), osteoblasts Sittinger et al, 2004), valvular interstitial cells (Masters et al, 2004), smooth muscle cells (Mann, 2003;Mann et al, 2001;Moffat and Marra, 2004;Ramamurthi and Vesely, 2005), fibroblasts (De Rosa et al, 2004;Shu et al, 2004;Zielinski and Aebischer, 1994), and mesenchymal stem cells (Lawson et al, 2004;Nuttelman et al, 2004;Schantz et al, 2003;Temenoff et al, 2004;Wang et al, 2003;Williams et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Factors that are often cited as being important include surface chemistry [1], hydrophobicity/ hydrophilicity [2,3], mechanical properties [4][5][6][7], surface energy [8], porosity [9], roughness [10][11][12][13][14][15] and charge [16,17]. Recently, we have been successful in designing experiments that allow us to produce sets of amphiphilic cross-linked materials (amphiphilic conetworks) that have different porosities (and related surface roughness) and are structured into nano-phase separated domains [18].…”
Section: Introductionmentioning
confidence: 99%